Dioecismo y Ciudad Ideal. Acerca de la República de Platón, VII 540e4-541a1 - Lévystone, David (Universidade de São Paulo, Department of Philosophy of the (USP, Brazil), 2022)
The radical mean suggested by Socrates in order to carry out the program of the Republic - the relegation to the fields of all inhabitants over the age of 10 - has perplexed modern commentators who have seen in it an ironical remark, a reductio ad absurdum presented in order to establish the very impossibility of Kallipolis or, on the contrary, a sign of the totalitarian and criminal character of the Platonic city. But it is far from evident, in view of political or military events prior and contemporary with the redaction of the Republic, that this solution could offend the moral conscience of fourth-century Greeks. This practice even seems to be the logical consequence of a certain oligarchic or aristocratic ideology, common by the end of the 5th c. and at the beginning of the 4th c., which associated, on the one hand, rural organization with the ‘best regime’ and, on the other, urban centralisation with democracy. The actual practices of the Lacedaemonian city, which maintained its primitive organization in komai, and even tried to impose it to other cities, could also serve as a model for the opponents of Athenian democracy. All of Plato's political models, from the Republic to the Laws, present cities whose essential, if not exclusive, productive activity is agriculture. The displacement of the population to the countryside seems, from this perspective, a rather serious proposal of the philosopher. * * Agradezco a Héctor Zagal y a María-Elena García-Peláez por sus observaciones y sugerencias al texto en español.
* Agradezco a Héctor Zagal y a María-Elena García-Peláez por sus observaciones y sugerencias al texto en español.
Keywords: Platón; República; Diocesismo; Ciudad ideal